An open-label study of the safety and tolerability of pazopanib in combination with FOLFOX6 or CapeOx in patients with colorectal cancer. - Brady, J; Corrie, P; Chau, I; Digumarti, R; Adams, L; Botbyl, J; Laubscher, K; Midgley, R; Mallath, M (2013)
BACKGROUND: Although combining targeted agents with conventional, first-line cytotoxic therapy has improved survival outcomes in patients with advanced colorectal cancer, further improvements in outcomes and tolerability are needed. METHODS: This phase I study evaluated the feasibility of combining oral pazopanib, an agent that targets multiple proangiogenic factors, with FOLFOX6 (oxaliplatin, leucovorin, and 5-fluorouracil) or CapeOx (oxaliplatin and capecitabine). This phase I study evaluated the optimally tolerated regimen of daily pazopanib (dose-escalated) plus standard FOLFOX6 or CapeOx in patients with advanced colorectal cancer. At the optimally tolerated regimen, each cohort was expanded to further evaluate safety and clinical response. RESULTS: The optimally tolerated regimens were pazopanib 800 mg plus FOLFOX6 and pazopanib 800 mg plus reduced CapeOx (capecitabine 850 mg/m(2)). The most commonly reported adverse events in the FOLFOX6 cohorts included decreased appetite, neutropenia, diarrhea, peripheral neuropathy, and vomiting. Similarly, the most commonly reported adverse events in the CapeOx cohorts included fatigue, vomiting, and decreased appetite. The overall response rate was 40 % (8/20 patients) in the pazopanib plus FOLFOX6 cohorts and 38 % (8/21 patients) in the pazopanib plus CapeOx cohorts. CONCLUSION: Pazopanib combined with FOLFOX6 or reduced CapeOx was adequately tolerated in this patient population.